Comparison of cervical acid phosphatase papanicolaou stain and standard papanicolaou stain as a screening tool for cancer cervix - E., Nandhini; R., Sasikala; Perumal, Varadharaja (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Carcinoma cervix is the second most common cancer in women (18%). Cervical smear by routine Papanicolaou (Pap) smear screening has significant rates of false-positive and false-negative results. To minimise this, we compare the efficacy of cervical acid phosphatase-papanicolaou (CAP-Pap) smear with conventional Pap smear in detecting premalignant lesions of cervix. The red-colored granules (enzyme coated abnormal cells) that are clearly detected, CAP-Pap positive aids in the quick and early diagnosis of aberrant cells, which speeds up the screening procedure Methods: The present observational study conducted among the patients presenting to gynaecology department for cancer cervix screening. Two cervical smears were collected for Pap and CAP-Pap staining. Cytology report showing abnormality either in Pap smear or CAP-Pap smear were subjected for colposcopy guided cervical biopsy after VIA/VILI and their results were correlated with histopathology reports as gold standard. Results: Total of 321 women were enrolled in the study. On comparison with Cervical biopsy, Pap smear had a sensitivity of 83.3%, specificity of 50%, Positive predictive value of 88.2%, Negative predictive value of 40.0%. CAP-Pap had a sensitivity of 100%, specificity of 50%, PPV of 90%, NPV of 100%. As evidenced by the 100% sensitivity, CAP-Pap meets the screening test criteria. Conclusions: The CAP- Pap test has a bright future as a rapid, inexpensive, and efficient method for initial screening or as an addition to Pap smear in primary health care of India for effective cervical cancer screening.